A case report of Leigh syndrome diagnosed by endomyocardial biopsy. Issue 2 (8th February 2021) - Maruo, Yuji; Ueda, Yuki; Murayama, Kei; Takeda, Atsuhito
Abstract: Background: Leigh syndrome is a neurodegenerative disorder caused by mitochondrial dysfunction with both phenotypic and genetic heterogeneity. Mitochondrial impairments are usually demonstrated by skeletal muscle biopsy. We report a case of Leigh syndrome diagnosed by endomyocardial biopsy (EMB), not by skeletal muscle biopsy. Case summary: At aged 7 months, the patient had delayed motor development. He developed metabolic acidosis triggered by an infection with elevated lactate and pyruvate values in serum and cerebrospinal fluid when he was 1 year old. T2-weighted imaging on magnetic resonance imaging of the brain revealed bilateral hyperintensity in midbrain and dorsal pons. Biopsied skeletal muscle did not show evidence of mitochondrial disease. Left ventricular hypertrophy, bilateral putamen hyperintensity in T2-weighted imaging and a lactate peak in the right basal ganglia in single voxel spectroscopy, and a convulsive seizure appeared at the age of 12, 15, and 16, respectively. When he was 17 years old, biopsied myocardium showed cytoplasmic vacuolization and a marked proliferation of mitochondria within myofibrils pathologically. Respiratory chain enzyme activity of the biopsied myocardium showed decreased activity of complex I. Genetic testing revealed an m.14453 A>G mutation on the MT-ND6 gene. He was finally diagnosed with Leigh syndrome. Administration of oral 5-aminolevulinic acid reduced the frequency of seizures. Discussion: EMB led to the diagnosis of Leigh syndrome. Efforts to find and conduct the biopsy of affected organs are important to diagnose mitochondrial disease. EMB is a useful diagnostic method when there is a difficulty in diagnosing mitochondrial disease by skeletal muscle biopsy.